Complement factor H: a novel innate immune checkpoint in cancer immunotherapy - Saxena, Ruchi; Gottlin, Elizabeth B.; Campa, Michael J.; Bushey, Ryan T.; Guo, Jian; Patz, Edward F.; He, You-Wen (Frontiers in Cell and Developmental Biology, 2024)
The elimination of cancer cells critically depends on the immune system. However, cancers have evolved a variety of defense mechanisms to evade immune monitoring, leading to tumor progression. Complement factor H (CFH), predominately known for its function in inhibiting the alternative pathway of the complement system, has recently been identified as an important innate immunological checkpoint in cancer. CFH-mediated immunosuppression enhances tumor cells' ability to avoid immune recognition and produce an immunosuppressive tumor microenvironment. This review explores the molecular underpinnings, interactions with immune cells, clinical consequences, and therapeutic possibilities of CFH as an innate immune checkpoint in cancer control. The difficulties and opportunities of using CFH as a target in cancer immunotherapy are also explored.